2018
DOI: 10.11648/j.ajma.20180602.12
|View full text |Cite
|
Sign up to set email alerts
|

Growing Fresh Water Microalgae in High Ammonium Landfill Leachate

Abstract: Municipal landfills are being employed for the disposal of communities solid waste. The compacted waste in landfills naturally generate leachate (liquid) which contain high concentrations of ammonium-nitrogen NH 4 +-N along with other toxic compounds. NH 4 +-N can be used as a cheap nitrogen source for microalgae biomass production, thereby facilitating tertiary treatment of landfill leachate. Two sets of studies, laboratory scale and pilot scale open raceway pond cultivation, were conducted to evaluate the po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 41 publications
0
3
0
2
Order By: Relevance
“…The TAN abatement in wastewater treatment is usually divided into different approaches: Physical (e.g., membrane separation), chemical (e.g., coagulation, solvent extraction, ion exchange,), and/or biological [23,56,79]. The high effective cost and energy consumption of technologies for one-step tertiary treatment of WWT represent a problem for industries and municipalities [80]. A valid alternative to conventional treatments may be provided by microalgae, coupling the nutrient removal from wastewater with the production of valuable biomass.…”
Section: Wastewater and Ammonium Contentmentioning
confidence: 99%
See 2 more Smart Citations
“…The TAN abatement in wastewater treatment is usually divided into different approaches: Physical (e.g., membrane separation), chemical (e.g., coagulation, solvent extraction, ion exchange,), and/or biological [23,56,79]. The high effective cost and energy consumption of technologies for one-step tertiary treatment of WWT represent a problem for industries and municipalities [80]. A valid alternative to conventional treatments may be provided by microalgae, coupling the nutrient removal from wastewater with the production of valuable biomass.…”
Section: Wastewater and Ammonium Contentmentioning
confidence: 99%
“…In wastewaters, N concentration must be reduced to acceptable limits (generally <10-15 mg L −1 depending on discharge point, population, and region regulation as described by regulation 91/271/CEE) before being released into the water body [83]. Many studies demonstrated that microalgae have a great potential for N removal and reported successful cultivations [13,[23][24][25]52,80]. Green microalgae (Chlorophyceae) represent the more exploited algae in WWT (Table 2).…”
Section: Microalgae In Wastewater Treatment For Ammonium Removalmentioning
confidence: 99%
See 1 more Smart Citation
“…Alguns estudos com microalgas registraram queda do pH. Khanzada et al (2018) cultivando Chlorella vulgaris e Chlamydomonas reinhardii no tratamento de lixiviado, identificaram que o pH estava constantemente diminuindo, atingindo 5,7. A redução do pH, também foi observado por Mustafa et al (2012) no cultivo de algas em lagoas com alta taxa de N-amoniacal usando lixiviado a 4%.…”
Section: Mev Das Esferas Com Algas Imobilizadasunclassified
“…L -1 -N-amoniacal), compostos orgânicos tóxicos, xenobióticos dissolvidos, baixa razão de demanda química e bioquímica de oxigênio (DBO5: DQO → 0,2 ou menos) e metais pesados (KHANZADA et al 2018). O Lixiviado é considerado uma água residuária de alta força iônica devido a nutrientes inorgânicos dissolvidos, o que pode levar à salinidade com aumento dos níveis de íons cloreto (~ 5g Cl -.…”
Section: Introductionunclassified